2019
DOI: 10.14502/tekstilec2019.62.269-277
|View full text |Cite
|
Sign up to set email alerts
|

Flame-retardant treatment of silk fabric with sodium phytate and chitosan using the layer-by-layer padding technique

Abstract: Bio-based fl ame-retardant agents and layer-by-layer assembly have attracted a great deal of attention in the fl ame-retardant fi elds of textiles, composites and polymeric materials. In this study, the electrostatic layer-by-layer assembly of chitosan and sodium phytate on silk fabric was carried out using a padding technique. The eff ects of the concentration and assembled bilayer of chitosan and sodium phytate on the weight gain, fl ammability, surface morphology, whiteness, stiff ness, lustre, tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…45 The authors recorded a 13.66% increase in fabric weight in the double-sided coating made using 0.5% chitosan by weight, whereas this increase was 24.81% when using 1.0% chitosan by weight. In this study, the observed weight gain was similar to the values reported by Lv et al 48 Since denim fabric is dyed, the amount of chitosan absorbed by the fabric was limited and chitosan could not penetrate into the fabric. In addition, the dense weaving of the denim fabric reduced the penetration of chitosan between the fibers.…”
Section: Structural Properties Of Crayfish Chitosan Coated Fabricssupporting
confidence: 90%
See 2 more Smart Citations
“…45 The authors recorded a 13.66% increase in fabric weight in the double-sided coating made using 0.5% chitosan by weight, whereas this increase was 24.81% when using 1.0% chitosan by weight. In this study, the observed weight gain was similar to the values reported by Lv et al 48 Since denim fabric is dyed, the amount of chitosan absorbed by the fabric was limited and chitosan could not penetrate into the fabric. In addition, the dense weaving of the denim fabric reduced the penetration of chitosan between the fibers.…”
Section: Structural Properties Of Crayfish Chitosan Coated Fabricssupporting
confidence: 90%
“…Mass losses are due to the loss of water in the first stage, the thermal decomposition of the cellulosic fabric in the second stage and the further decomposition of the degraded products in the third stage. 48 The burning properties of cellulosic fibers vary significantly related to their chemical composition. 52 The results of this study also confirm the previous data.…”
Section: Analysis Results Of Chitosan-coated Fabricsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing public awareness of environmental issues, eco-friendly bio-based IFR coatings have been reported to construct on textiles. Phytic acid (PA), DNA and chitosan (CH) have been used for the construction of the bio-based IFR coating [30][31][32]. We have studied to construct IFR coating on PET fabrics by positively charged chitosan and negatively charged ammonium polyphosphate [33].…”
Section: Introductionmentioning
confidence: 99%
“…The coated polyester fabric achieved excellent dripping-resistance, while its flame retardancy was unsatisfactory. PA as a green, renewable, sustainable natural flame retardant has been reported to flame retardant treatment for cotton, silk and wool fabrics [27][28][29].…”
Section: Introductionmentioning
confidence: 99%